2022
DOI: 10.1186/s12889-022-13826-1
|View full text |Cite
|
Sign up to set email alerts
|

The association between the presence of fast-food outlets and BMI: the role of neighbourhood socio-economic status, healthy food outlets, and dietary factors

Abstract: Background Evidence on the association between the presence of fast-food outlets and Body Mass Index (BMI) is inconsistent. Furthermore, mechanisms underlying the fast-food outlet presence-BMI association are understudied. We investigated the association between the number of fast-food outlets being present and objectively measured BMI. Moreover, we investigated to what extent this association was moderated by neighbourhood socio-economic status (NSES) and healthy food outlets. Additionally, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…This could have resulted in underestimated associations because participants who did not attend the follow-up visit had a higher BMI than those who did. Besides, we had data available for residential fast- research in Lifelines has shown that the impact of this temporal mismatch is limited [27]. Furthermore, the follow-up period of approximately 4 years was relatively short to assess associations between fast-food environments and BMI change.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This could have resulted in underestimated associations because participants who did not attend the follow-up visit had a higher BMI than those who did. Besides, we had data available for residential fast- research in Lifelines has shown that the impact of this temporal mismatch is limited [27]. Furthermore, the follow-up period of approximately 4 years was relatively short to assess associations between fast-food environments and BMI change.…”
Section: Discussionmentioning
confidence: 99%
“…Results may further have been affected by temporal mismatch between measurement of fast‐food exposure (2012) and baseline BMI (2006 to 2013). Still, 85.2% of participants were recruited between 2010 and 2013, and previous research in Lifelines has shown that the impact of this temporal mismatch is limited [27]. Furthermore, the follow‐up period of approximately 4 years was relatively short to assess associations between fast‐food environments and BMI change.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[12] Van erpecum et.al found evidence that participants who had one fast-food outlet had a higher BMI than participants with no fast-food outlets. [13] Furthermore Newby PK et,al. detailed in their study that the consumption of meat and potatoes caused an annual change in BMI (0.30+/_ /0.06) and in waist circumference was more than 3 times as great for subjects in the white-bread cluster. [14] Third, the less consumption frequency (1 time or < 1 time / day) of the certain foods such as Juice, energy drinks, coffee, or sweetened beverages was 18.2%, Desserts, like chocolate or ice cream, and other sweet foods was 23.3%, and Fried food/or packaged snacks was 17.6% noted among the college girls (Table 3).…”
Section: Discussionmentioning
confidence: 99%